Impacts of water regulation on Tenualosa ilisha in the Narmada Estuary, Gujarat, India - Bhakta, Dibakar; Meetei, Wakamban Anand; Vaisakh, Gopinathan; Das, Sanjoy Kumar; Manna, Ranjan Kumar (Journal of Fisheries, 2018)
Hilsa is a highly prestigious fish for esteemed delicious taste, high market demand and price. It forms an important fishery of funnel-shaped 72 km long Narmada Estuary. Rapid decline in hilsa catch has been recorded in the Narmada Estuary over last few decades. Hilsa catch was recorded 5180 ton in 2006–07 that reduced to only 419 ton in 2014–15. Pre-impoundment of dam showed that T. ilisha contributed to the tune of 977.1 to 3727 ton from 1974–75 to 1982–83 and the highest catch of hilsa was 15319 ton during 1993–94. Sardar Sarovar Dam started functional in the year 1994 which has impacted natural water flow of the river and resulted in a reduction of freshwater availability in the estuary; the development of sand bars at the mouth of the estuary also reduced the tidal ingress into the system; low depth, loss of breeding, nursery and feeding grounds, over fishing may be the most important factors affecting hilsa fishery in Narmada estuary. Catching of juvenile hilsa during winter by ‘Golava’ net (small meshed bag net) also led to a rapid decline in hilsa catch.